Zn–VI quasiparticle gaps and optical spectra from many-body calculations. (24th April 2017) - Riefer, A; Weber, N; Mund, J; Yakovlev, D R; Bayer, M; Schindlmayr, Arno; Meier, C; Schmidt, W G
Abstract: The electronic band structures of hexagonal ZnO and cubic ZnS, ZnSe, and ZnTe compounds are determined within hybrid-density-functional theory and quasiparticle calculations. It is found that the band-edge energies calculated on the G 0 W 0 (Zn chalcogenides) or GW (ZnO) level of theory agree well with experiment, while fully self-consistent QS GW calculations are required for the correct description of the Zn 3 d bands. The quasiparticle band structures are used to calculate the linear response and second-harmonic-generation (SHG) spectra of the Zn–VI compounds. Excitonic effects in the optical absorption are accounted for within the Bethe–Salpeter approach. The calculated spectra are discussed in the context of previous experimental data and present SHG measurements for ZnO.